Feeding Rate and Mortality Impact of Crystals and Endospores Versus Crystals – Producing Recombinants of Bacillus thuringiensis Against Cotton Leafworm - Alotaibi, Saad A. (International Journal of Biotechnology for Wellness Industries, 2013)
Two Bacillus strains belonging to two species; thuringiensis and subtilis were used in this study. These strains were genetically marking and to be used in conjugation process depending upon the opposite genetic markers to induce recombinants in both strains. This study aimed to evaluate two bioinsecticides induced from recombinants; crystals, crystals + endospores, which derived from two strains of Bacillus and four of their transconjugants resulted from conjugation between Bacillus thuringiensis and Bacillus subtilis, with respect to their toxicity against lepidopterous cotton pest. The results obtained in this study achieved that endospores were effective in reducing feed consumption at the late times of larval age, in contrast, crystals was more effective in reducing feed consumption at the early times of larval age. The results appeared that endospores play a major role in increasing insecticidal activity of bioinsecticides (crystals), this leading to use their in all bioinsecticides. Endospores were effective in reducing the average weight of surviving larvae more than crystals. This indicated that bioinsecticides containing endospores + crystals were more effective than that containing crystals alone. However, most bioinsecticides containing endospores were reduced the average weight of surviving larvae at 48, 72 and 96 hours from treatment. All bioinsecticides containing crystals + endospores were more effective in reducing survival percentage than that containing crystals alone. This achieved that bioinsecticides containing crystals + endospores were more toxic on S. littoralis larvae. The mean number of mortality larvae appeared in treatments with crystals + endospores was more than that caused by bioinsecticides containing crystals alone. In most treatments done in this study the insecticidal activity of crystals + endospores caused higher mortality larvae than that caused by bioinsecticides containing crystals alone.